Comparison of health-related quality of life (HRQoL) among healthy, obese and chronically ill Iranian children - Sara Jalali-Farahani; Fahimeh Alsadat Shojaei; Parnian Parvin; Parisa Amiri (BMC, 2018)
Abstract Background Health-related quality of life (HRQoL) has frequently been compared between both healthy and obese children and healthy and chronically ill children; however, there is glaring lack of evidence regarding comparison of HRQoL in obese children with their counterparts with chronic diseases. Therefore, this study aimed to compare HRQoL among healthy, obese and chronically ill children. Methods This cross sectional study was conducted among 802 children (8-12 years) who were recruited via convenience sampling method. Participants were 98 healthy, 102 obese and 602 chronically ill children with six groups of chronic conditions including different types of cancer, rheumatoid arthritis, chronic gastrointestinal, kidney, neurologic and respiratory diseases. HRQoL was assessed using the Iranian version of the PedsQL questionnaire and both reports including child self-report and parent proxy-report were obtained. To compare subscales and total scores of HRQoL among healthy, obese and six groups of chronically ill children, the general linear model was used. Results Mean self-reported HRQoL total scores were 73.7 ± 13.3 and 74.6 ± 11.8 in girls and boys respectively; based on the parents' reports, mean HRQoL total scores were 71.6 ± 15.4 and 71.4 ± 13.0 in girls and boys respectively. From the prespectives of both children and parents, HRQoL total score was significantly lower in obese girls compared to both healthy girls and girls with chronic gastrointestinal, kidney, neurologic and respiratory diseases. Considering both children's and parents' reports, HRQoL total score was significantly lower in obese boys compared to both healthy boys and boys with chronic respiratory diseases. In terms of subscales of HRQoL, the impairment of HRQoL in obese children, compared to their counterparts with other chronic diseases, was more common in social functioning and physical functioning subscales, specifically in girls. Conclusion Obese children reported poorer HRQoL compared to their healthy counterparts, as well as their counterparts with chronic diseases. Current findings emphasize the important impact of childhood obesity on the perceived health of these children, particularly in the social dimension, underscoring thereby the designing, planning and implementation of health promotion programs for prevention and treatment of childhood obesity.